Code Switching in Sigapokna Language Uttered by Minangkabau People in Sigapokna, Mentawai - Marno Marno; Raflis Raflis; Fetri Reni (Jurnal Ilmiah Pendidikan Scholastic, 2019)
This research contains the title "Code Switching in Sigapokna language changed by Minangkabau people in Sigapokna" viewed from a structuralism perspective, this research discusses language contact occurring in bilingual or multilingual communities, because in this society it uses more than one language. The occurrence of language code switching in Sigapokna is due to the mixing of two languages ​​between the Sigapokna language and the Minangkabau language, native speakers of the Minangkabau people who settled in Sigapokna. Limited to some basic ideas related to observation into three questions as follows: (1) What is the form of code switching in the Sigapokna language, (2) What is the Sigapokna matrix in Minangkabau speakers, (3) What are the causes of code switching in the Sigapokna language. used is from Nababan about sociolinguistics used to answer the purpose of this research. For data analysis methods, the research used is a qualitative and quantitative approach. This approach emphasizes the meaning and understanding of the mind, reasoning, definitions of certain situations (in some contexts), more to examine matters relating to daily life such as the culture of an area. The purpose of research is usually related to practical matters. Data analysis is also a process of simplifying data into forms that are easier to read and interpret to look for broader meanings and implications from the results of research over language codes in Sigapokna. Data collection techniques in this research, to get the data and information needed, researchers used literature research techniques. In literature studies, researchers use techniques that are played with interviews and record data, materials, or references related to the problem and purpose of the research. Using library research techniques in finding data relevant to the subject of analysis. From the data collected amounted to 563. Data in the Minangkabau language form was mixed with 280 and the language while in the Sigapokna language form was 283. From the collection, the matrix language was 280/283×100% of the Minangkabau language. Sigapokna language is mixed with Minangkabau 283 so, it can be concluded that the mixed Sigapokna language is 283/280 × 100%. The occurrence of language contacts or code switching depends on the location or where someone lives. If someone is in an area with different languages ​​and cultures, there will automatically be a code transfer between the speaker, the speech partner and the speech partner in order to avoid a misunderstanding. From the conclusion of the code switching data above, native Minangkabau speakers are more dominant using the Sigapokna language.